2015
DOI: 10.1177/1934578x1501000830
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity-guided Separation of the Active Compounds in Acacia Pennata Responsible for the Prevention of Alzheimer's Disease

Abstract: The objective of this study was to evaluate the health benefits of plants used in Thai food, specifically Acacia pennata Willd., in Alzheimer's prevention. A. pennata twigs strongly inhibited -amyloid aggregation. Bioactivity-guided separation of the active fractions yielded six known compounds, tetracosane (1), 1-(heptyloxy)-octadecane (2), methyl tridecanoate (3), arborinone (4), confertamide A (5) and 4-hydroxy-1-methyl-pyrrolidin-2-carboxylic acid (6). The structures were determined by spectroscopic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…The LC–ESI-MS analysis revealed that flavonoids were the major phytoconstituents present in the leaves of A. pennata which is in alignment with the previous phytochemical reports (Kim et al 2015 ; Lomarat et al 2015 ) and this could probably be the main reason of its DNA protection effect as revealed from the current study that APE possess the potential to counteract the genotoxic effect of acetaminophen on liver tissues, while acetaminophen treatment revealed significant upregulation in tumour suppressor gene (p53), multidrug resistance (mdr1b) gene (Fig. 3 ) and ROS generation (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The LC–ESI-MS analysis revealed that flavonoids were the major phytoconstituents present in the leaves of A. pennata which is in alignment with the previous phytochemical reports (Kim et al 2015 ; Lomarat et al 2015 ) and this could probably be the main reason of its DNA protection effect as revealed from the current study that APE possess the potential to counteract the genotoxic effect of acetaminophen on liver tissues, while acetaminophen treatment revealed significant upregulation in tumour suppressor gene (p53), multidrug resistance (mdr1b) gene (Fig. 3 ) and ROS generation (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The fragment ion of kaempferol aglycone at m / z 285 is due to the loss of glucose and rhamnose units attached to the same position of the aglycone [M–H-162-146]¯. Therefore, it was tentatively identified as kaempferol 3- O -rhamnopyaranosyl-(1→4)-glucopyranosyl previously isolated from the leaves of A. pennata (Dongmo et al 2007 ; Lomarat et al 2015 ). Peak 7 showed a deprotonated molecular ion [M–H]¯ at m / z 609.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results were consistent with previous studies that Acacia pennata contained a high content of flavonoid and phenolic compounds [ 46 , 47 ]. Acacia pennata had various biological activities such as anti-nociception against pain [ 48 ], anti-inflammation through inhibition of cyclooxygenases-1 and -2 enzyme activities due to the flavonoid compositions [ 49 ], anti-cancer of pancreas and prostate [ 50 ], prevention of liver damage after acetaminophen-induced genotoxicity [ 51 ], and anti-Alzheimer disease by prevention of β-amyloid aggregation [ 52 ]. In addition, Acacia pennata crude extract at 245 mg/L could kill the larvae and pupae of Aedes aegypti mosquito, which is a potent dengue vector [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, A. pennata has been shown to exhibit anti-nociceptive, anti-inflammatory, antioxidant, anti-parasitic, and anti-transcription activity [2]. A. pennata was also found to have 5 compounds with inhibitory activity for β-amyloid aggregation and could be beneficial for Alzheimer's prevention [3]. As part of an ongoing search screening for anti-HIV-1 PR drugs from Vietnamese medicinal plants, we report in this work the isolation, structural elucidation, and anti-HIV-1 PR activity of a new saponin triterpene (1), as well as the known saponin pitheduloside G (2), isolated from the stems of A. pennata.…”
mentioning
confidence: 99%